As origens da Lei Antiterrorismo: os tortuosos caminhos da localização das normas internacionais de combate ao terrorismo no Brasil - France, Guilherme de Jesus (2017)
The passing of the Antiterrorism Law in Brazil represents a unique moment in its history. Tracing the origins of said legislation depends on understanding the development of international norms on the fight against terrorism as well as previous instances in which domestic norms on the subject played a role domestically. Using Securitization theory and IR’s literature on norm diffusion, I intend to draw the international normative framework in which Brazil finds itself in order to understand how these norms played an essential part in sparking the legislative process which would result in the Antiterrorism Law. A wider discussion on the relations between the Brazilian State and its population is necessary, however, so that one can understand the historical resistance to legislation of that kind. Especially relevant is the fear related to the criminalization of social movements, derived from various historical experiences, among which I highlight the military dictatorship period. Specific instances in which both legislators and law enforcement officials repressed social movements will be presented, with an emphasis on recent experiences in rural areas (the Landless Rural Workers Movement – MST) and also in urban areas (widespread protests starting in 2013). Previous instances in which efforts were made to produce legislation on terrorism will be detailed as well. On its own, it is the first narrative of its kind, relating the actions inside the federal government, especially since 2006, on the issue. Some of the dynamics identified would also repeat themselves in the legislative process that generated the Antiterrorism Law. In 2015, the actions of the Financial Action Task Force (FATF), which intended to see its Recommendations implemented, were instrumental in setting off said process, which can thus be understood as the localization of international norms on terrorism. Once international pressure was recognized the drawing of legislation began inside the executive branch, where the Ministry of Justice and the Council for Financial Activities Control prevailed in elaborating a bill that suited the FATF’s needs, but did not threaten social movements. In that moment, however, other interests also became apparent, as others inside the government had different agendas – the Armed Forces, the Institutional Security Office, the Brazilian Intelligence Agency, the Federal Police and the Parquet. Once sent to Congress, Bill 2016/2015 suffered deep changes, as congressmen intervened and those institutions attempted, for a second time, to have their interests prevail. Debates focused on a number of specific points such as the definition of terrorism, a provision to safeguard social movements, the criminalization of preparatory acts and the development of a coordination mechanism on terrorism prevention and repression. Drawing on official documentation, some of it previously unseen, international and Brazilian academic works and, especially, on over 25 interviews conducted with people involved in different aspects of the legislative process, I intend to determine the origins of the Antiterrorism Law in Brazil.